Genetic testing for congenital non-syndromic sensorineural hearing loss. (September 2019) - Raymond, Mallory; Walker, Elizabeth; Dave, Ishaan; Dedhia, Kavita
Abstract: Introduction: Approximately 60% of congenital pediatric hearing loss is of genetic etiology. To evaluate non-syndromic sensorineural hearing loss (NSSNHL), guidelines emphasize the use of comprehensive genetic testing (CGT) with next generation sequencing (NGS), yet these tests have limited accessibility, and potential CGT results may not be well understood. Thus, our objective was to analyze genetic testing practices and results for pediatric patients with NSSNHL. Methods: This was a retrospective chart review of pediatric patients (<18 years) diagnosed with NSSNHL from 2014 to 2017 at a tertiary pediatric hospital. Demographics, clinical data, CGT results, genetic testing practices and referral patterns were recorded and descriptively analyzed. Logistic regression models identified patient characteristics associated with pathogenic variants (PV) and variants of unknown significance (VOUS). Results: 430 patients with congenital NSSNHL were included in the study. Genetic testing was ordered for 28% (n = 122) and resulted for 16% (n = 68). Most of the ordered tests (89%, n = 109) were the CGT panel. A majority (62%, n = 97) of the time in which genetic testing was not ordered, a referral for genetics consultation was placed. Amongst those with CGT results, a definitive genetic etiology was identified in 25% (n = 13), with less than half due to variants of GJB2/6 . At least one PV was identified for 33% (n = 18), while at least one VOUS for 93% (n = 51). There were no significant differences in PV presence or number of VOUS across any characteristic except race. When compared to Caucasians, African Americans had significantly higher rates of VOUS with a rate ratio and 95% CI of 1.61 [1.11–2.34], p = 0.01, and Asians trended towards higher rates (1.96 [0.95–4.05], p = 0.06). Conclusions: CGT is of high utility in the identification of relevant genetic variants and definitive genetic etiologies for pediatric patients with NSSNHL. Though guidelines recommend the early use of CGT, there are many barriers to appropriate testing and counseling, leading to low rates of CGT use at this single institution.